Manual Recovery of a Sea Ice Based Ocean Profiler - Katlein, Christian; Labaste, Matthieu; Hoppmann, Mario (Frontiers in Marine Science, 2019)
Ice-tethered ocean profiling systems are an essential tool for the year-round observation of physical and biogeochemical properties of the Arctic Ocean. Despite being considered expendable equipment due to the challenging logistics, their recovery is attractive mainly due to two factors: If the sensors can be retrieved, this allows for their post calibration, which helps to assess sensor drift and biofouling. In addition, the recovery of such expensive equipment can ease off financial pressure on autonomous ocean observation programs by enabling the reuse of central elements after refurbishment. Here we present a method how such profiling systems can be recovered from sea ice by 3 people in about 4 hours, without the on-site availability of a fully-equipped vessel. The presented technique combines rope techniques from mountain rescue applications with lightweight equipment and procedures similar to those used for the deployment of such instruments. We provide a detailed description of the whole process, provide suggestions for potential improvements as well as suggestions towards improved instrument design favoring recoverability of future deployments. We conclude that good preparation and practice of the relevant rope procedures is critical to mission success and that a well selected range of necessary equipment makes the process much more efficient.